The effect of lacosamide on bone tissue in orchidectomised male albino Wistar rats - Šimko, Julius; Fekete, Soňa; Maláková, Jana; Kremláček, Jan; Horáček, Jiří; Živná, Helena; Palička, Vladimír; Živný, Pavel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
AIMS: While most antiepileptic drugs (AEDs) have been associated with various adverse effects on bone health, for the recently introduced lacosamide (LCM) no corresponding data have been published. The present study evaluates the effect of LCM on bone mineral density, bone turnover markers, and bone mechanical strength in a rat model. METHODS: 16 orchidectomized Wistar rats were divided into control and experimental groups, 8 rats each. Dual energy X-ray absorptiometry was used to measure bone mineral density (BMD). As bone metabolism markers, the concentrations of bone markers were assayed in bone homogenate. In addition, both femurs were measured and used for biomechanical testing. RESULTS: Compared to the control group, we found lower BMD in the experimental group in the area of the left (8%) as well as the right femur (12%), all differences being statistically significant. In both femur diaphyses, but not in lumbar vertebrae, BMD was lower in the LCM group, suggesting a preferential effect on cortical bone. However, neither the thickness of the diaphyseal cortical bone nor the fragility in biomechanical testing was different between the groups. Of the bone metabolism markers, the significant decline was in procollagen type I N-terminal peptide (PINP) levels (37.4%), suggesting a decrease in osteoid synthesis. CONCLUSION: We assume then that long-lasting exposure to LCM can represent a certain risk to the health of bone in the setting of gonadal insufficiency. Further studies will be needed to confirm these findings and to determine how high the risk will be in comparison to the other AEDs.
Keywords: acetamidy; Animals; Epilepsy; absorpční fotometrie; Rats, Wistar; Absorptiometry, Photon; Anticonvulsants; kostní denzita; Bone Density; kosti a kostní tkáň; antikonvulziva; Femur; Acetamides; biomechanika; femur; epilepsie; Male; modely nemocí na zvířatech; Disease Models, Animal; krysa rodu Rattus; zvířata; mužské pohlaví; Bone and Bones; Rats; Biomechanical Phenomena; potkani Wistar